Angiotensina-(1-7): efeitos sinérgicos e antagônicos sobre a sinalização da aldosterona no cardiomiócito - Pedro William Machado de Almeida (2015)
High serum levels of aldosterone have been linked to the development of cardiac disease. In contrast, angiotensin (Ang)-(1-7) was extensively shown to possess cardioprotective effects, including the attenuation of cardiac dysfunction induced by excessive mineralocorticoid activation in vivo, suggesting possible interactions between these two molecules. Here, we investigated whether there is cross-talk between aldosterone and Ang-(1-7) and its functional consequences for calcium (Ca2+) signaling in ventricular myocytes. Short-term effects of aldosterone on Ca2+ transient were assessed in Fluo-4/AM-loaded myocytes. Confocal images showed that Ang-(1-7) had no effect on Ca2+ transient parameters, whereas aldosterone increased the magnitude of the Ca2+ transient. Quite unexpectedly, addition of Ang-(1-7) to aldosterone-treated myocytes further enhanced the amplitude of the Ca2+ transient suggesting a synergistic effect of these molecules. Aldosterone action on the amplitude of the Ca2+ transient is mediated by protein kinase A, which acts modulating both the ICa current density, and phospholamban phosphorylation on serina16. Phospholamban is a key regulator of SERCA activity. Both changes were not altered by Ang-(1-7). When cardiomyocytes were exposed to aldosterone, increased Ca2+ spark rate was measured. Ang-(1-7) prevented this change. In addition, a NO synthase inhibitor, L-NAME, restored the effect of aldosterone on Ca2+ spark rate in Ang-(1-7)-treated myocytes and attenuated the synergistic effect of these two molecules in the Ca2+ transient. Increased reactive oxygen species, and altered mineralocorticoid and glucocorticoid receptor mRNA levels were also characteristic of aldosterone exposed myocytes. Ang-(1-7) antagonized all these changes. Furthermore, Ang-(1-7) effects on Ca2+ handling in aldosterone treated myocytes were mediated by nitric oxide. Ang-(1-7) effects on NO production correlated with increased eNOS and nNOS phosphorylation in cardiac myocytes. Taken together, these results indicate that NO plays an important role in Ang-(1-7) and aldosterone cross-talk. Our results bring new perspectives in the understanding of how two prominent molecules with supposedly antagonist cardiac actions cross-talk to synergistically amplify Ca2+ signals in cardiomyocytes.